A SURVEY OF THE LEVEL OF SATISFACTION OF MILDLY DISABLED CHILDREN IN LEARNING SPORTS AT SMPLB BINA UPAYA KESEJAHTERAAN PARA CACAT (BUKESRA) YEAR 2024 - Amani, Raissa; S.Pd.,M.Pd, Ifwandi; M.Pd.,AIFO, Dr.Muhammad Iqbal (Sport Pedagogy Journal, 2025)
Physical education is not only for normal children but children with disabilities or children with special needs are also entitled to physical education. In some cases, children with disabilities can have significant communication barriers, creating challenges in interacting with the outside world. Physical activity contributes to physical and mental well being. The purpose of this study is to find out all the shortcomings and obstacles that exist. This research is a descriptive study with a quantitative approach with a survey method and with a population consisting of SMPLB BUKESRA students in the mild tunagrahita category totaling 25 by taking samples through the total sampling technique. Data collection was carried out using questionnaire data collection techniques. The questionnaire used is a closed questionnaire using a guttman scale. Based on the results of research data collection, it can be concluded that the level of satisfaction of mild tunagrahita children on sports learning at SMPLB BUKESRA is 85.6%. With the confidence variable (confidence)which is the most / dominant affecting the satisfaction of mild tunagrahita children in sports learning at SMPLB BUKESRA by 90%.Keywords: Mild Tunagrahita, Satisfaction, Sports Learning.